Exploring sector-specific sustainability indicators: a content analysis of sustainability reports in the logistics sector. Issue 3 (15th October 2021) - Jayarathna, Chamari Pamoshika; Agdas, Duzgun; Dawes, Les; Miska, Marc
Abstract : Purpose: Businesses produce corporate sustainability information in support of the decision-making of their stakeholders through sustainability reporting. However, the use of such information has been limited because of the broadness of sustainability indicators used in sustainability reports. This study aims to identify sector-specific sustainability indicators and priorities based on the material issues of the logistics sector. Design/methodology/approach: The authors conducted an exploratory study using 64 sustainability reports from the logistics sector. Qualitative content analysis was performed using Leximancer software to identify key themes and material concepts of sustainability reports. Findings: The results showed that the most important indicators of the logistics sector are economic performance and energy, yet sustainability reports appear to focus more on reporting social sustainability information. Of the several sustainability measures, environmental and social factors dominated the reporting (8 economic, 62 environmental and 58 social). This discrepancy can also imply inconsistencies in sustainability reporting. Practical implications: Identifying sector-specific indicators enables assessing the impact of sustainability issues on value creation and performance comparison among similar organizations. This is also beneficial in ensuring consistency of sustainability reporting, which is a prerequisite for policymaking in sustainable logistics. Originality/value: Prior studies emphasized that no sector-specific sustainability indicators were established in the literature and standardized indicators are needed to ensure the comparability of results. This study addresses this gap by identifying sector-specific sustainability indicators based on the material issues of the logistics sector.